Development of Web-based Learning Media For Vocational High School (SMK) Negeri 3 Bengkulu City - Dino Oktariandi Sopa; Rozali Toyib; Khairullah; Nuri David Maria Veronika (Jurnal Komputer, Informasi dan Teknologi, 2025)
This research aims to develop web-based learning media that can be used at SMK Negeri 3 Bengkulu City motivated by the need to improve the quality of learning in the digital era, where technology can be an effective tool to support the teaching and learning process. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model development method which consists of five stages, namely needs analysis, learning media design, media development, implementation, and evaluation of the effectiveness of the developed media. The results of this web-based learning media development include materials presented interactively, with features such as quizzes, learning videos, and discussion forums that can facilitate communication between teachers and students. In addition, the responses from teachers and students to the use of this learning media are also positive, with most stating that this media can increase students' interest and motivation to learn. Based on the evaluation results, this learning media is expected to be implemented more widely in SMK Negeri 3 Kota Bengkulu and other schools, to support more interactive and efficient teaching in the future.